An investigation into the use of computer-based technology in schools around Mankweng District, Limpopo Province - Makwela, David Modibe (My University, 2006)
The purpose of this study is to share with the scholars, various institutions, government, particularly the teachers in Mankweng, on the use of computer-based technology in schools around Mankweng District. The study looks into issues such as computers in schools, computers in teaching, negative aspects on computer usage and policy in schooling context. The study further provides information on the assessment, values and ethics for computer-based technology use, elimination of reluctance in using computers, teachers’ resistance attitude considering the infusion of computers, which is globally an issue of concern, is also being highlighted. The background on the curriculum change, from traditional ways of teaching to the development of the new curriculum (OBE),is advocated briefly and to the point. There is also data analysis, interpretation and presentation and the summary of findings, conclusion and recommendations. It was against this background that a study of this nature was undertaken. The main two-fold aim was to investigate the impact of computer-based technology in teaching and the interaction between the teacher and the computer. There is a tendency among teachers to ignore the use of computers. However, not all teachers ignore the use of computers. The study was conducted at the Mankweng Circuit of the Limpopo Province. A questionnaire was used as an instrument to collect data. The results indicated that most teachers have insufficient training, fear losing authority and have misconceptions, which are the main reasons of not using these technologies. Therefore, continuous training and ongoing support will help to keep abreast in preparing learners for the work place.
Thesis (M.Dev.) -- University of Limpopo, 2006
Keywords: Investigation; Computer; Schools; Technology; Cyberinfrastructure; Computer assisted instruction -- South Africa.; Educational technology -- South Africa; Teaching -- Aids and devices